Bimetallic Niobium-Based Catalysts Supported on SBA-15 for Hydrodeoxygenation of Anisole - Ballesteros-Plata, Daniel; Barroso-Martín, Isabel; Medina Cervantes, Juan Andrés; Maciel, Carmen; Huirache-Acuña, Rafael; Rodríguez-Castellón, Enrique; Infantes-Molina, Antonia (ACS, 2021)
The effect of adding iron, cobalt or nickel to a prepared niobium-supported catalyst using mesoporous silica SBA-15 as a support was evaluated in the hydrodeoxygenation (HDO) reaction of anisole, chosen as a model compound in lignocellulosic biomass derived bio-oil. HDO activity as well as selectivity toward O-free products were highly dependent on the catalyst formulation: Ni incorporation showed the highest anisole conversion and selectivity to deoxygenated products, followed by Co and Fe counterparts. The activity was explained in terms of acidity, metal surface exposure and reducibility as a function of the interaction between the phases present. Regarding the characterization results, the better performance of NiNb/SBA-15 was associated with its lower acidity, higher Nb/Si surface exposure, NbO2/Nb2O5 ratio and better interaction between Ni and Nb species.
Keywords: Compuestos aromáticos; Catalizadores; Acidity; Aromatic compounds; Catalysts; Redox reactions